Hypoparathyroidism: Working toward Effective Treatment - Buckley, Rita (MD Conference Express, 2013)
Hypoparathyroidism is a rare endocrine disorder with a wide range of etiologies, including surgery and radioactive iodine therapy. It can be acquired or genetic; curable or permanent. This article describes the differential diagnosis of the disease, summarizes the latest knowledge about the various causes of acquired hypoparathyroidism, and reviews recognized genetic mutations. The article also discusses skeletal and nonskeletal hypoparathyroidism.